The Zalew Balaton Quarry geosite in Trzebinia, southern Poland: an update of geological data - Kamieniarz, Sylwester (Geotourism/Geoturystyka, 2015)
A development project of the Zalew Balaton area is being presently carried out. One of the project assumptions is to create a geological path across the object. However, detailed data about the geological structure of this place is not available. For this reason, the author has researched and updated the information about the rocks occurring in the walls of the old quarry. Primarily, terrain (textural and structural analysis, layers strike and dip measurements, geological boundaries delimitation) and laboratory analysis (X-Ray Powder Diffraction, microscopic rock samples analysis) were conducted. Collected data was afterwards compared with available literature. Within the steep slopes of excavation, strong-karsted, faulted Upper Jurassic (Oxfordian) carbonate sediments were revealed. These are massive, platy and crumpled limestone. These rocks could be deposited in changing conditions of sedimentation, when calm carbonate sedimentation was disturbed by underwater gravity flows, as demonstrated by their detrital character. One of the karst funnel on the northern slope was fi lled with Oligocene sand. As a result, groundwater fl uctuations created a sarsen structure, popularly called the “Wielbłąd”. In relation to the planned geological path across the Zalew Balaton area, previous knowledge should be supplemented with new data, respectively processed and included on information panes, located within object. Plans of the path should pay attention to potential geotouristic safety, as well as to the geological values of the protected object, during its future modernization.